Additional fertilizer and nematicide combinations on upland cotton to manage Rotylenchulus reniformis and Meloidogyne incognita in Alabama - Gordon, Kara L.; Schrimsher, Drew W.; Lawrence, Kathy S. (Journal of nematology, 2022)
Plant parasitic nematodes are major pests on upland cotton worldwide and in the United States. The reniform nematode, and the southern root-knot nematode are some of the most damaging nematodes on cotton in the United States. Current management strategies focus on reducing nematode populations with nematicides. The objective of this research was to integrate additional fertilizer and nematicide combinations into current practices to establish economical nematode management strategies while promoting cotton yield and profit. Microplot and field trials were run to evaluate fertilizer and nematicide combinations applied at the pinhead square (PHS) and first bloom (FB) plant growth stages to reduce nematode population density and promote plant growth and yield. Cost efficiency was evaluated based on profit from lint yields and chemical input costs. Data combined from 2019 and 2020 suggested a nematicide seed treatment (ST) ST + (NH SO + Vydate C-LV + Max-In Sulfur was the most effective in increasing seed cotton yields in the microplot trials. In field trials, a nematicide ST + (NH SO + Vydate C-LV at PHS supported the largest lint yield and profit per hectare at $1176. In field trials, a nematicide ST + 28-0-0-5 + Vydate C-LV + Max-In Sulfur at PHS and FB supported the largest lint yields and profit per hectare at $784. These results suggest that combinations utilizing fertilizers and nematicides applied together across the season in addition to current fertility management show potential to promote yield and profit in and infested cotton fields.